Raw Materials for Archaeological Pottery from the Campania Region of Italy: A Petrophysical Characterization. Issue 5 (22nd July 2013) - De, Alberto; Grifa, Celestino; Cultrone, Giuseppe; De, Pantaleone; Langella, Alessio; Morra, Vincenzo
<x xml:space="preserve">Abstract</x> We performed petrophysical analyses on 34 clayey samples of different geological origin within the Campania region of Italy in order to determine possible sources of raw materials used to produce ancient pottery. Possible raw material sources can be grouped into high‐CaO clays (HCC) and low‐CaO clays (LCC). HCC are mainly represented by more recent (Miocene‐Pleistocene) basinal sediments whereas LCC tend to be associated with basinal, alluvial, and pyroclastic deposits. A chemical comparison between clayey raw materials, modern ceramic replicas, and Campanian archaeological ceramics of several typologies (common ware, cooking ware, fine tableware, amphorae, and bricks) from 8th century B.C. to the Middle Ages (a total of 350 ceramic samples) indicates that HCC were extensively used for common wares and that these were either mixed with temper or levigated. In contrast, most of the LCC were used for the production of cookware. We also analyzed the technological potential of the sampled raw materials, taking into consideration their actual and possible uses. We observed that most HCC deposits were well suited for tableware and amphorae, whereas LCC were better for cookware and some fine tableware.